The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.3390/agronomy3040595
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus simplex—A Little Known PGPB with Anti-Fungal Activity—Alters Pea Legume Root Architecture and Nodule Morphology When Coinoculated with Rhizobium leguminosarum bv. viciae

Abstract: Two strains, 30N-5 and 30VD-1, identified as Bacillus simplex and B. subtilis, were isolated from the rhizospheres of two different plants, a Podocarpus and a palm, respectively, growing in the University of California, Los Angeles (UCLA) Mildred E. Mathias Botanical Garden. B. subtilis is a well-known plant-growth promoting bacterial species, but B. simplex is not. B. simplex 30N-5 was initially isolated on a nitrogen-free medium, but no evidence for nitrogen fixation was found. Nevertheless, pea OPEN ACCESSA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(84 citation statements)
references
References 68 publications
6
77
0
1
Order By: Relevance
“…Bacillus simplex strains were reported to have PGP activities and have been isolated as endophytes from various plants and also reisolated from pea nodules in coinoculation experiments with Rhizobium leguminosarum bv. viciae (Schwartz et al 2013 and references therein). Deep analyses of NAB genomes may provide insights into understanding the involvement of many understudied microbes in plant growth and survival.…”
Section: Non-nodulating Root Nodule Inhabitantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacillus simplex strains were reported to have PGP activities and have been isolated as endophytes from various plants and also reisolated from pea nodules in coinoculation experiments with Rhizobium leguminosarum bv. viciae (Schwartz et al 2013 and references therein). Deep analyses of NAB genomes may provide insights into understanding the involvement of many understudied microbes in plant growth and survival.…”
Section: Non-nodulating Root Nodule Inhabitantsmentioning
confidence: 99%
“…Also, nodules of Hedysarum, a forage legume, were found to harbor Enterobacter cloacae, Enterobacter kobei, Escherichia vulneris, Pantoea agglomerans, and Leclercia adecarboxylata (Muresu et al 2008). Because it has long been known that coinoculation of rhizobia and other bacteria, particularly Bacillus species, promotes not only nodulation (Schwartz et al 2013 and papers cited therein), but also N availability in sustainable agricultural systems (Rajendran et al 2012), it is assumed that many of the nonpathogenic bacteria found within nodules or in plant tissues as endophytes could be safe and effective partners for enhancing nitrogen fixation in legumes (Sturz et al 2000).…”
Section: F1mentioning
confidence: 99%
“…Our data show that root exudates significantly affect microbial abundance in soil, as reported elsewhere [31]. Given that members of the Bacillus genus exhibit PGP activities [24,32], we used 13k/19k to co-inoculate the seeded substrates. The co-inoculum caused an increase in the total number of microorganisms in 100% OS from 2.45x10 6 to 3.12x10 6 CFU/g (oat) and from 2.02x10 6 to 3.12x10 6 CFU/g (lettuce) (Fig.…”
Section: Effect Of 13k/19k Co-inoculation On Overburden Bacterial Commentioning
confidence: 77%
“…To our knowledge, this represents the first microbial characterization of mine waste in BiH. Previous research has demonstrated the ability of B. simplex to accumulate metals, such as Cd, Co, Ni, and Sr [36], as well as to promote plant growth by altering plant root architecture, i.e., by stimulating the emergence of more lateral roots [24]. Studies have also shown PGP activities of B. cereus [37] and other group members, such as B. thuringiensis [38], as well as the potential role of B. thuringiensis in biodegradation of organophosphorus in contaminated soil [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation